2017
DOI: 10.1080/23328940.2017.1381800
|View full text |Cite
|
Sign up to set email alerts
|

Screening criteria for increased susceptibility to heat stress during work or leisure in hot environments in healthy individuals aged 31–70 years

Abstract: Population aging and global warming generate important public health risks, as older adults have increased susceptibility to heat stress (SHS). We defined and validated sex-specific screening criteria for SHS during work and leisure activities in hot environments in individuals aged 31-70 years using age, anthropometry, and cardiorespiratory fitness. A total of 123 males and 44 females [44 ± 14 years; 22.9 ± 7.4% body fat; 40.3 ± 8.6 peak oxygen uptake (mlO/kg/min)] participated, separated into the Analysis (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Our estimate that 35% of individuals working in heat stress conditions experience occupational heat strain is in line with the 30% (95% CI 24-36) prevalence reported for increased susceptibility to heat stress (an inability to mitigate hyperthermia) when working or exercising in hot environments, 139 and with epidemiological data 140,141 for morbidity and mortality during extreme heat events. When compared with normative values for healthy, [142][143][144] obese, 145 or acutely-ill 146 adults, the average core temperature of 37•6°C estimated for individuals working a shift under heat stress is considered borderline hyperthermia or pyrexia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our estimate that 35% of individuals working in heat stress conditions experience occupational heat strain is in line with the 30% (95% CI 24-36) prevalence reported for increased susceptibility to heat stress (an inability to mitigate hyperthermia) when working or exercising in hot environments, 139 and with epidemiological data 140,141 for morbidity and mortality during extreme heat events. When compared with normative values for healthy, [142][143][144] obese, 145 or acutely-ill 146 adults, the average core temperature of 37•6°C estimated for individuals working a shift under heat stress is considered borderline hyperthermia or pyrexia.…”
Section: Discussionsupporting
confidence: 89%
“…While core temperature thresholds for hyperthermia, fever, and heat injury vary across individuals, 144 those who are older, obese, unfit, have chronic disease, or experience acute illness or infection are at a high risk for heatinduced pathologies (eg, heat cramps, heat exhaustion, and heat stroke). 1,7,139,147 We used the standard definitions of kidney disease and acute kidney injury proposed by the KDIGO clinical practice guidelines workgroup 24 and found that 15% of individuals working in heat stress have these conditions, which is markedly higher than the prevalence rates reported for kidney disease (10%) 148 and acute kidney injury in high-income (2%) 149,150 and low-income (3-9%) 151,152 countries. Taken together, these results raise serious concerns for the kidney function of individuals who typically or frequently work in heat stress conditions, because even a single episode of acute kidney injury can lead to chronic kidney disease, with substantial socioeconomic and public health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors further concluded that safety programs and strategies should be developed in response to high occurrences of heat-related injury in tropical regions [69]. In addition, efforts have been made to identify the characteristics of those susceptible to heat-related injury to prevent public health risks [70]. This may include older workers and those working for successive days in the heat [71].…”
Section: Discussionmentioning
confidence: 99%
“…High aerobic fitness levels can counteract age-related impairments in whole-body heat loss during exercise (Flouris et al, 2018;Stapleton et al, 2015). Habitual physical activity can also reduce age-related oxidative stress and enhance endothelium-dependent vasodilation (Pierce et al, 2011;Walker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%